On the Erosion of France’s National Values (Liberté, Egalité, Fraternité) - Basri, Muhammad Ridha (Universitas Islam Internasional Indonesia (UIII), 2024)
The Republic, Secularism and Security France versus the Burqa and the Niqab by Raphael Cohen-Almagor. Switzerland: Springer. 2022. This book contributes significantly in explaining ambivalence or paradoxical situations in France. Through its motto (liberté, égalité, fraternité), the country has been promoting and implementing liberalism and secularism for many years, yet at the same time, the country is increasingly illiberal, as shown by its policy banning the burqa and niqab in 2010.